Single-dose pharmacokinetics of temocillin in plasma and soft tissues of healthy volunteers after intravenous and subcutaneous administration: a randomized crossover microdialysis trial. (20th May 2020) - Matzneller, Peter; Ngougni Pokem, Perrin; Capron, Arnaud; Lackner, Edith; Wulkersdorfer, Beatrix; Nussbaumer-Pröll, Alina; Österreicher, Zoe; Duchek, Michael; Van de Velde, Sebastien; Wallemacq, Pierre E; Mouton, Johan W; Van Bambeke, Françoise; et al.
Abstract: Background: The antibiotic temocillin has recently been rediscovered as a promising therapeutic option against MDR Gram-negative bacteria. However, some aspects of the pharmacokinetic (PK) profile of the drug are still to be elucidated: subcutaneous administration of temocillin might be of interest as an alternative to the intravenous route in selected patients. Similarly, information on the penetration of temocillin into human soft tissues is lacking. Objectives: To investigate the feasibility and plasma PK of subcutaneous dosing as well as soft tissue PK of temocillin after intravenous administration to healthy volunteers. Methods: Eight healthy volunteers received 2 g of temocillin both as intravenous and subcutaneous infusion in a randomized two-period crossover study. Concentration–time profiles of total temocillin in plasma (after both routes) and of unbound temocillin in plasma, muscle and subcutis (only after intravenous dosing) were determined up to 12 h post-dose. Results: Subcutaneous dosing caused some infusion site discomfort but resulted in sustained drug concentrations over time with only slightly decreased overall exposure compared with intravenous dosing. Plasma protein binding of temocillin showed concentration-dependent behaviour and was higher than previously reported. Still, unbound drug concentrations in muscle and subcutis determined by microdialysis markedly exceeded those in plasma, suggesting good tissue penetration of temocillin. Conclusions: The subcutaneous administration of temocillin is a valid and feasible alternative to intravenous dosing. With the description of plasma protein binding and soft tissue PK of temocillin in healthy volunteers, this study provides important information that adds to the ongoing characterization of the PK profile of temocillin and might serve as input for PK/PD considerations.